2003
DOI: 10.1046/j.1524-475x.2003.11212.x
|View full text |Cite
|
Sign up to set email alerts
|

Standardized qualitative evaluation of scar tissue properties in an animal wound healing model

Abstract: There is a great need to establish reproducible methods for evaluative studies of wound treatment and wound healing. Validation of the healing process through optical techniques, as well as histologic and immunohistochemical methodologies, have been improved and to some extent have become well-established assays. Data relating to biomechanical properties, e.g., evaluation of the tensile strength of scar tissue that forms in experimental wound treatment strategies, are less widely available. We chose the domest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…In the present study, we also found that a 230 mT static magnetic treatment of the wound increased the wound breaking strength compared with sham magnet group. It implied that SMF could help to improve the quality of wound healing; similar results had also been reported in previous studies [7, 15]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, we also found that a 230 mT static magnetic treatment of the wound increased the wound breaking strength compared with sham magnet group. It implied that SMF could help to improve the quality of wound healing; similar results had also been reported in previous studies [7, 15]. …”
Section: Discussionsupporting
confidence: 87%
“…This parameter of the skin also exhibits a progressive increase in continual tissue repair during the wound healing process [15]. In the present study, we also found that a 230 mT static magnetic treatment of the wound increased the wound breaking strength compared with sham magnet group.…”
Section: Discussionsupporting
confidence: 80%
“…These properties are similar to the differences in human beings between skin sites with a high density of arterioles and venules and sites with predominantly nutritive capillary perfusion. Although pig skin is more physiologically similar to the human skin (Hollander et al 2003), the high cost and our inexperience with porcine husbandry make it prohibitive to use a porcine model. Previous studies in rat models produced valuable results (Herrman et al 1999, Li et al 2006, Kwan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Facial morphological changes, such as sagging, are also thought to be associated with an increase of body fat percentage (2). in its response to external stress and in its internal organization (4). The increase in the weight burden as a result of accumulated fat and increased numbers of adipose cells is speculated to weaken the supporting function of the dermis.…”
Section: Introductionmentioning
confidence: 99%